In-vitro and in-vivo anti-inflammatory activity of Andrographis serpyllifolia (Rottl. Ex Vahl.) Wt. - Kandati, Vasu; Govardhan, P; Reddy, Ch Siva; Nath, A Ravinder; Reddy, R R (International Current Pharmaceutical Journal, 2012)
The study was aimed to evaluate the analgesic and anti-inflammatory activity (by both in-vitro and in-vivo) of both chloroform and methanol root extracts of Andrographis serpyllifolia (Rottl. Ex Vahl.) Wt. Methods used for the studies were In-vitro 5-Lipoxygenase inhibition assay and In-vivo measurement of rat paw edema and ear edema in rats, acetic acid induced writhing response and hot plate method in albino mice. Chloroform and methanolic extracts of A. serpyllifolia root have shown moderate potency in inhibiting 5-LOX and shown significant anti-inflammatory activity. Despite the IC50 values are little higher, anti-inflammatory efficacy of these extracts possibly due to other mechanisms apart of 5-LOX inhibition. However, In-vivo anti-inflammatory studies revealed that A. serpyllifolia methanolic extract has shown higher degree of efficacy when compared to the chloroform extract. In terms of analgesic activity in writhing test, methanolic extract has shown more efficacy than chloroform extract. Hence, it is important to isolate the active principles for further testing the anti-inflammatory efficacy. DOI: http://dx.doi.org/10.3329/icpj.v1i8.11250 International Current Pharmaceutical Journal 2012, 1(8): 199-204